TIMBULAN DAN KOMPOSISI SAMPAH DI KAWASAN PERKANTORAN DAN WISMA (Studi Kasus: Werdhapura Village Center, Kota Denpasar, Provinsi Bali) - Made W. Wardiha; Pradwi S. A. Putri; Lya M. Setyawati; Muhajirin Muhajirin (Environmental Research Center (PPLH) of Udayana University, 2014)
Solid waste is one of the potential problems in Bali Province. One of the waste sources in urban areas especially Denpasar is the office and hotel/inn/guesthouse. Werdhapura Village Center is one of the office and hotel areas in Denpasar. Werdhapura management does not have an integrated waste management. Therefore, it should be made an integrated waste management plan started by doing study about waste generation and composition. The purpose of this study is to investigate the generation and waste composition in Werdhapura and estimate the potential amount of waste that can be managed. The study starts from surveys and interviews regarding the waste sources and existing condition of waste management in Werdhapura. The surveys conducted by reviewing the trash facilities, waste temporary site, and the sources of waste, while the interviews conducted to Werdhapura Management. Waste generation and composition measured by using SNI 19-3964-1995 method. The result showed that waste generation is about 4.6 m/day of volume, and about 302.3 kg/day of weight. Waste composition (%weight) the most is food waste (26.43%), paper (18.55%), residue (14.64%), and organic waste (10.93%). About 47.51% of total waste in Werdhapura was potentially to recycle that is organic waste, food waste, and dry waste.